Transport Policies and Development - Berg, Claudia N.; Deichmann, Uwe; Liu, Yishen; Selod, Harris (Taylor and Francis, 2017)
This survey reviews the current state of the economic literature, assessing the impact of transport investments and policies on growth, inclusion, and sustainability in a developing country context. It also discusses the specific implementation challenges of transport interventions in developing countries.